CARBON FOOTPRINT IN THE TEXTILE INDUSTRY - Salas C., G. (2009)
We can achieve a climate neutrality with the reduction of CO2 emmisions in the controlled process. The rest is compensated with Carbon Bonds and MDL proyects. The objective is to give our customers products that do not generate a “carbon footprint”. The program utilizes the methods described in the Green House Gas Protocol (GHG Protocol), an has developed their emissions inventory. Direct emmisions are 3.6 kg CO2 eq/kg and indirect emmisions are 10,8 kg de CO2 eq/kg